Drying-Cocoa, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
A picture of workers on a cocoa estate spreading the cocoa beans for drying in the sun on a series of cocoa houses. These cocoa houses have sliding roofs that protect the beans from rain.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa houses